2019
DOI: 10.1186/s12866-019-1561-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of multiple influx and efflux transporters in the accumulation of cationic fluorescent dyes by Escherichia coli

Abstract: Background It is widely believed that most xenobiotics cross biomembranes by diffusing through the phospholipid bilayer, and that the use of protein transporters is an occasional adjunct. According to an alternative view, phospholipid bilayer transport is negligible, and several different transporters may be involved in the uptake of an individual molecular type. We recognise here that the availability of gene knockout collections allows one to assess the contributions of all potential transporter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 190 publications
0
59
0
Order By: Relevance
“…Many efflux transporters are sufficiently active that even when the drug has relatively tight intracellular binding sites they can effectively remove almost all of it, as is the case with AcrAB/TolC and ethidium bromide 73, 74 . A recent experimental survey of several hundred gene knockouts in E. coli , using fluorescent probes as antibiotic surrogates showed that dozens of such efflux transporters could be active and thereby contribute to lowering the steady-state uptake 47 . There is also considerable redundancy and plasticity 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efflux transporters are sufficiently active that even when the drug has relatively tight intracellular binding sites they can effectively remove almost all of it, as is the case with AcrAB/TolC and ethidium bromide 73, 74 . A recent experimental survey of several hundred gene knockouts in E. coli , using fluorescent probes as antibiotic surrogates showed that dozens of such efflux transporters could be active and thereby contribute to lowering the steady-state uptake 47 . There is also considerable redundancy and plasticity 75 .…”
Section: Discussionmentioning
confidence: 99%
“…it has the capability of raising the concentration of the drug of interest to a higher level inside than outside. Such transporters necessarily require a source of free energy; in prokaryotes this is mainly ATP 46, 47 . The effluxer is also taken to be ATP-driven.…”
Section: Introductionmentioning
confidence: 99%
“…[97][98][99]). As an illustr ation, and as a com plem ent to our detailed gene knockout studi es [17], Table 1 gives an indication of dyes w hose inter action w ith specific tr anspor ter s has been dem onstr ated dir ectly. In som e cases, thei r sur r ogacy as a substr ate for a tr anspor ter w ith a know n non-fluor escent substr ate is clear , and as m entioned in the intr oduction they ar e som etim es r efer r ed to as 'false fluor escent substr ates'.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]). Ou r sp ecific in ter est h er e is in th e tr a n sp or ter -m ed ia ted m ean s b y w h ich sm a ll flu or escen t m olecu les en ter livin g cells, a n d ou r in ter est h a s b een stim u la ted b y th e r ecogn ition th a t a given p r ob e m a y b e a su b str a te for a la r ge va r iety of b oth in flu x a n d efflu x tr a n sp or ter s [17]. Efflu x tr a n sp or ter s a r e often fa ir ly p r om iscu ou s, sin ce th eir job is la r gely to r id cells of u n w a n ted m olecu les th a t m a y h a ve en ter ed , a lth ou gh th ey ca n a n d d o h a ve oth er , im p or ta n t p h ysiologica l r oles (e.g.…”
mentioning
confidence: 99%
“…As part of a wide-ranging study into the nature of transporter substrates (e.g. (Dobson and Kell, 2008;Jindal et al, 2019;Kell et al, 2013;Kell et al, 2011;Kell and Oliver, 2014;), we recognised that the approach of Gründemann and colleagues (Gründemann et al, 2005) could be an ideal strategy for implementation using modern, high-resolution metabolomics methods. We have previously developed low-resolution methods for determining the human serum metabolome reliably (Broadhurst and Kell, 2006) and over extended periods Dunn et al, 2011;Kenny et al, 2010;Zelena et al, 2009), including the extensive use of QA/QC samples.…”
Section: Introductionmentioning
confidence: 99%